The Relationship of Family Support to the Motivation of Elderly Patients with Hypertension in Undergoing Treatment at Telaga Biru Health Center - Nurdinda Daola; Rona Febriyona; Andi Nur Aina Sudirman (Universitas Muhammadiyah Palu, 2026)
Hypertension is one of the health problems experienced by many elderly people and has the potential to cause serious complications if not treated optimally. One of the factors that affect the success of hypertension treatment is the motivation of the elderly, which can be strengthened through family support. This study aims to analyze the relationship between family support and the motivation of the elderly in undergoing hypertension treatment at the Telaga Biru Health Center. This study uses a type of quantitative research with a cross-sectional approach. The sample of this study was 48 elderly using purposive sampling techniques. This data was collected using questionnaire interviews by assessing four dimensions of family support (emotional, instrumental, informational, and assessment) and four indicators of elderly motivation (medication adherence, blood pressure monitoring, physical activity, and dietary regulation). This study uses the chi-square test. The results showed that most of the respondents received family support in the good category (64.6%) and had a high level of motivation (70.8%). The results of the chi-square test showed that there was a significant relationship between family support and the motivation of the elderly (p value = 0.014 < ? = 0.05), which means that the higher the family support, the higher the motivation of the elderly in undergoing hypertension treatment. The results of the study show that family support has an important role in increasing the motivation of the elderly in undergoing hypertension treatment. Therefore, family involvement through continuous education from health facilities is an aspect that needs to be considered in an effort to improve the quality of life of the elderly and prevent complications.